Are perceived bad working conditions and perceived workplace bullying associated with doctor visits? Results of the nationally representative German General Social Survey - André Hajek; Hans-Helmut König (BMC, 2019)
Abstract Background The reason for doctor visits associated with bad working conditions (and workplace bullying) remains unknown. Therefore, the aim of this study was to examine the association between perceived working conditions as well as workplace bullying and the number of doctor visits as well as the reason for seeing a doctor. Methods Data were derived from the German General Social Survey, a representative cross-section of the population in the year 2014. Self-reported doctor visits in the last 3 months were used as outcome measure. Self-rated working conditions (noise, bad air; time/performance pressure; bad working atmosphere; overtime; shifts/night work; hard physical labour) and workplace bullying were assessed. The reason for seeing a doctor was also recorded (acute illness; chronic illness; feeling unwell; requesting advice; visit to the doctor's office without consulting the doctor (e.g., need to get a prescription); preventive medical check-up/vaccination). Regression analysis stratified by sex was conducted. Results Adjusting for various potential confounders, Poisson regressions showed that workplace bullying was associated with increased doctor visits in men, but not in women. Contrarily, time/performance pressure at work was only associated with increased doctor visits in women, but not in men. Furthermore, the probability of visiting the doctor for reasons of acute illness or feeling unwell increased with workplace bullying in men. The probability of visiting the doctor because of feeling unwell increased with time/performance pressure in women. Conclusions Our findings stress the association between adverse working conditions (workplace bullying as well as time/performance pressure at work) and doctor visits, with remarkable gender differences. Longitudinal studies are required to confirm the present findings and to obtain further insights into this relationship.